SAOLhist.se – för allmänt och vetenskapligt bruk - Holmer, Louise; Malmgren, Sven-Göran; Martens, Monica von (Nordiske Studier i Leksikografi, 2018)
The Swedish Academy Glossary (Svenska Akademiens ordlista, SAOL), a normative glossary with particular focus on spelling, inflexion, and pro-nunciation, has appeared since 1874. In 2006, the 13th edition appeared. The second, third, fourth and fifth editions were more or less reprints of the first edition. Thus, the 2006 edition may be regarded as the ninth (au-tonomous) SAOL edition. The most important parts of these nine edi-tions, especially the complete sets of lemmas, have been transformed into a database. The database may be thought of as a matrix with more than 200 000 rows and eleven columns (the nine SAOL editions plus the Dalin dictionary, plus a column to the left with all lemmas that have occurred in at least one SAOL edition). The interface is very flexible, allowing the inclusion of other dictionaries. From each square of the matrix there is a link to a facsimile version of the full corresponding dictionary article. Several advanced searches are possible, e.g.: which words were added and omitted between any two consecutive editions, or: has the frequency of a particular suffix increased or decreased over time?